The kindness curriculum : stop bullying before it starts - Rice, Judith, 1953- (St. Paul, MN : Redleaf Press, 2013)
"Use this comprehensive framework and developmentally appropriate activities to teach young children compassion, conflict resolution, respect, and other positive, pro-social values as you cultivate a peaceful and supportive learning environment for all children"--
6. Self-control : Simon says ; The great predictor ; Recycled timers ; Turn taking ; Potion lotion ; Stop, go, and slow necklace ; Penguins ; Choo-choo game ; My day at school ; The talking wand -- 7. Friendship : Hi and bye child ; Friendship fruit soup ; Shake shake shake ; Firefly game ; Best smile ; Friendship map ; Hug a bug ; Fishing for friends ; Let's play -- 8. Conflict resolution : Helping hands ; What can we do? ; My turn, your turn ; Problem-solving table ; Kid cards ; Turtle puppets and story ; The stop song ; Mr. Peepers's chants ; Learning to ask for help -- 9. Visualization : Imaging ; Goal pictures ; Audio recordings ; Thinking hats ; Worry objects ; Practical visualizations -- 10. Parent and child home sweet homework : Creating calm ; Love ; Feelings and empathy ; Gentleness ; Respect ; Self-control ; Friendship ; Conflict resolution ; Visualization ; Television literacy for preschoolers -- Appendixes : A. Reproducible forms : The kindness coupon book ; Blank face picture ; Six feeling faces ; My day at school ; Helping hands pledge ; Kid cards -- B. Common American Sign Language signs -- Recommended resources.
Includes bibliographical references.
Keywords: Moral education (Early childhood); Social values -- Study and teaching (Early childhood); Early childhood education -- Activity programs; EDUCATION -- Preschool & Kindergarten; FAMILY & RELATIONSHIPS -- Interpersonal Relations; EDUCATION -- Philosophy & Social Aspects; Instructional and educational works; Instructional and educational works